A new species of the ammonite genus Neochetoceras Spath (Oppeliidae) from the Hybonotum Zone (Lower Tithonian) of Southern Germany, with comments on the phylogeny of the genus - Scherzinger, Armin (2015)
Fil: Fil: Scherzinger, Armin. Eberdingen, Germany